A Study on the Usefulness of Stochastic Simulation Algorithms for Teaching and Learning in College Physical Education Classrooms. (23rd September 2022) - Xu, Ju
Abstract : In order to address the problem of the absolute nature of the evaluation of superiority and inferiority in the evaluation of physical education classroom in universities and the problem of inconsistency in the conclusion of multiple evaluations, we develop an "autonomous advantage evaluation method to highlight one's own advantages, " which uses a probabilistic stochastic simulation algorithm to evaluate the advantages of the evaluated objects by calculating the degree of superiority among them. The method is based on an innovative "base to top" approach, with a high degree of independence. The method was validated by means of an algorithm, and the conclusions were obtained with probabilistic information.